Studi Kualitas Pelayanan Pengujian Kendaraan Bermotor Di Dinas Perhubungan Komunikasi dan Informatika Kota Semarang - Afrizal Afrizal; Endang Larasati; Dyah Hariani (Journal of Public Policy and Management Review, 2015)
Good serviceis a requirement of all the people, in the middle of the fact that the service given the current bureaucracy tends convoluted, expensive, unfriendly, etc. There for, the government should beable to answer the needs of the citizenfor the maximum service, various improvements need to be done. Department of Communicationand Informatics Semarang cityincluding one that runs the service unit for vehicle testing service, to thequality of vehicle testing services need to know in order to get an idea of how the service provided Department of Communicationand Information Semarang city. This study aims to determine the quality service of Department Transportation, Communication and Informatics Semarang city based on theory Zaithaml et al. which consists of five dimensions, namely Tangibles (direct evidence), Reliability (Reliability), Responsiveness (Responsiveness), Asurance (Guarantee), and Emphathy (Empathy). The study was conducted with qualitative descriptiv. Based on the research results, the quality of vehicle testing services performed Department of Transportation Communication and Informatics Semarang city is good, how ever there are two limiting factor, that is the destruction of sometesters vehicle, causing a lack of collateraland lack of decent test HR and HR age testers vehicle causing productivity less than the maximum. Thus the advice that can be given that immediate repair of the damaged equipment so that there is guarantee that the vehicle tested definitely worthand coordinate with the Ministry of Transportation and other relevantin stitutions regarding the short age of human resources vehicle testers. Expected future, Department of Communication and Information Semarang can provide better service.